2012
DOI: 10.1038/pj.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of fiber structure development of poly(butylene terephthalate) in a continuous laser-heated drawing process

Abstract: The structural development of poly(butylene terephthalate) (PBT) fibers was analyzed using in situ wide angle X-ray diffraction and fiber temperature measurements during CO 2 laser-heated drawing, in which the necking position on the running fiber could be fixed by CO 2 laser irradiation. The measured parameters were determined as functions of the elapsed time after necking with a time resolution of 0.3 ms. The as-spun PBT fibers, which exhibited a low-oriented a-crystalline structure, were drawn to a draw rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The α structure is often formed when the material is crystallized or heat-treated in a relaxed state, while the β structure is formed instead when the material is under stress. 34,35 Both crystal structures can be transformed to each other, depending upon the stretched or relaxed treatment of the materials. 33 From the method of polymer treatment and diffraction patterns, we can conclude that the PBIT copolyesters with ≤40 mol % IS content purified by HFIP/ methanol recrystallization possess α crystal structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The α structure is often formed when the material is crystallized or heat-treated in a relaxed state, while the β structure is formed instead when the material is under stress. 34,35 Both crystal structures can be transformed to each other, depending upon the stretched or relaxed treatment of the materials. 33 From the method of polymer treatment and diffraction patterns, we can conclude that the PBIT copolyesters with ≤40 mol % IS content purified by HFIP/ methanol recrystallization possess α crystal structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A schematic of the CO 2 laser irradiated drawing system used in this study is shown in Fig. , a detailed explanation of which can be found in our previous papers . The CO 2 laser beam, which was generated by a PIN‐20S laser source manufactured by Onizuca Glass, was irradiated onto the running fiber.…”
Section: Methodsmentioning
confidence: 99%
“…When this deformation occurs in the neck region, the fiber diameter decreases rapidly, molecular chains align to the fiber axis, and the fiber structure is developed through orientation‐induced crystallization, all in just a few milliseconds. There have been several reports on the structure development by CO 2 laser irradiated neck drawing of various synthetic fibers, and our research group has studied the fiber structure development though in situ characterization of X‐ray diffraction .…”
Section: Introductionmentioning
confidence: 99%
“…The α-form can change into the β-form with an all-trans (ttt) conformation when the polymer is subjected to stress [ 43 ]. Nevertheless, the β-form is unstable because, after the removal of the stress, the β-form returns to the α-form [ 44 , 45 ]. The smectic phase occurs when amorphous PBT is stretched at room temperature and transforms into the α-form upon heating [ 45 ].…”
Section: Introductionmentioning
confidence: 99%